Penerapan Model Problem Based Learning dalam Pembelajaran Berdiferensiasi berdasarakan Gaya Belajar Peserta Didik pada Pelajaran IPAS Kelas V Sekolah Dasar - Ningrum, Sistia; Huda, Choirul; Susanto, Joko Heri; Musyafanah, Qoriati (Education Journal : Journal Educational Research and Development, 2024)
This study aims to implement differentiated learning based on students' learning styles with the Problem Based Learning learning model as a step to meet the needs of diverse learning styles of students in the classroom. Qualitative descriptive research with the Triangulation method was used in this study. Qualitative descriptive research is used to provide an overview of the conditions at the research location so that people can see and understand the research environment. A total of 28 students of class V B SD N Palebon 01 were used as subjects of this study. The source of data collection is based on interviews, observations, and learning style questionnaires. Based on the learning style questionnaire for class V B, it is known that there are 36% of students in class V B who have an auditory learning style and 32% of students with visual and kinesthetic learning styles. The Problem Based Learning learning model includes five syntaxes, namely, Problem orientation, organizing students, guiding individual or group investigations, developing and presenting work results, and evaluating the problem-solving process. In the process of differentiated learning based on learning styles with the problem based learning model, the results showed that there was good enthusiasm in the learning process. Different activities for students in each learning style group are aimed at fulfilling the diversity of students' learning needs. Students are taught to learn in a way that suits their learning style, so that they can explore the material they are studying in their own way and make learning more meaningful. From the results of the research and discussion, namely the use of the Problem Based Learning learning model for differentiated learning based on learning styles in class V B SD Negeri Palebon 01 in an effort to fulfill the diversity of student needs can have a positive impact on student learning. Through various teaching and learning activities that are adjusted to the competencies of each student, students appear enthusiastic in learning